A new framework for integrated climate finance and inclusive responses to sustainable development in Malaysia - Ibrahim, Kamarulazizi; Ahmad Shabudin, Ahmad Firdaus; Kanayathu, Chacko Koshy; Ghassem, R. Asrar (Taylor & Francis Open, 2016)
With Malaysia’s commitment to both mitigation and adaptation, the 21st Conference of Parties to the United Nations Framework Convention for Climate Change in Paris, 2015, will be both an opportunity to showcase best practices and a forum to promote international ownership of climate challenge before it becomes a catastrophe. Our experience with weather extremes is that the best time to intervene is at the risk level via prevention and preparedness, compared to any wait-and-see approach. As the Honourable Prime Minister of Malaysia, Dato’ Sri Mohd Najib Abdul Razak, elaborated during the recent 11th Malaysia Plan presentation to the parliament, ‘such an approach has to be seen as part of adopting green growth and increasing our commitment to long-term sustainability’. Malaysia is also aware that this requires policy support, technological interventions and financial commitment. It is for this reason the Malaysia’s pledge at the Copenhagen COP-15 was to reduce its carbon emission by 40% from 2005 levels by 2020, subject to technology transfer and financial support by developed countries. Having achieved a 33% reduction in the last five years, Malaysia is convinced that it can reach the 40% target following an inclusive partnership framework for action.